2011
DOI: 10.3801/iafss.fss.10-889
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pyrolysis Behavior Results between the Cone Calorimeter and the Fire Propagation Apparatus Heat Sources

Abstract: The cone calorimeter and the fire propagation apparatus (FPA) are often used to carry out flammability studies of materials. There are various differences in the set-up of these two devices that could lead to different fire behaviour for the same material. Among these, the impact of the different heat sources used is studied here. The cone calorimeter employs an electrical cone heater and the FPA uses tungsten lamps to radiate a given heat flux level to the sample. Experiments are conducted in the FPA set-up u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 14 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Bal and Rein extended the work of Jiang et al to consider the possibility of other parameters affecting the ignition time at high flux but again showed that it is influenced mainly by in‐depth absorption. In a related work, differences in the pyrolysis behavior induced by a cone heater or the FM Global Fire Propagation Apparatus (FPA) are discussed .…”
Section: Introductionmentioning
confidence: 99%
“…Bal and Rein extended the work of Jiang et al to consider the possibility of other parameters affecting the ignition time at high flux but again showed that it is influenced mainly by in‐depth absorption. In a related work, differences in the pyrolysis behavior induced by a cone heater or the FM Global Fire Propagation Apparatus (FPA) are discussed .…”
Section: Introductionmentioning
confidence: 99%
“…For irradiance values lower than 50 kW.m −2 , the decomposition and charring of the condensed phase occur without any type of sustained flaming combustion. Therefore, the heating of the material and its reaction rate are only controlled by the intensity level of the radiant heat source . It seems natural that when the imposed irradiance level at the surface of the material is reduced, the amount of energy received and thus the temperature rise will be lower on the surface and in depth.…”
Section: Resultsmentioning
confidence: 99%
“…This function is minimal at the surface Y F,s (0, t ). The in‐depth degradation depends on the spectral characteristic of the heat source, the radiative properties of the polymer and more particularly on its emissivity and on its transmissivity, defined on Figure by the absorption coefficient κ( x , t ) . Generally the emission spectra of large flame are continuous in the infrared.…”
Section: Fire Behaviour At Materials Scalementioning
confidence: 99%